The philosophy of illumination : a new critical edition of the text of Hikmat al-Ishraq - Suhrawardī, Yaḥyá ibn Ḥabash, 1152 or 1153-1191.; Walbridge, John. 567821; Ziai, Hossein. (Provo, Utah : Brigham Young University Press, 1999)
Includes bibliographical and references